Dipolar and quadrupolar characteristics of shear transformation in two dimensional metallic glasses. (March 2023) - Shi, Rong-Hao; Wu, Yi-Cheng; Shuang, Fei; Zhang, Zhi-Wei
Abstract: Localized shear transformation (ST), a fundamental and ubiquitous plastic phenomenon in metallic glasses (MGs), is still an enigma because of intrinsic entangling of shear, dilatation, and rotation. Here, to unveil this mystery, we formulate a theoretical protocol based on quadrupolar Eshelby inclusion supplemented by simulations of two-dimensional (2D) Lennard-Jones MGs and wavenumber spectrum analysis, revealing that only STs of pure shear or tension are well-known quadrupoles, whereas STs of torsion or simple shear exhibit strongly dipolar characteristics, which are the physical-mathematical explanations for shear-induced dilatation and shear-vortex coupling. Initial ST events are quadrupoles including shear and dilatation. As spatiotemporal coupling intensifies, ST is gradually dominated by dipoles and vortices, contributed to self-assembly and percolation. Our findings reinforce the inherent correlation between evolution of quadrupolar/dipolar characteristics and plastic deformation of MGs, providing fundamental understandings for localized amorphous flow events. Graphical Abstract: ga1 Highlights: Four possible local plastic perturbations of two-dimensional (2D) shear transformation (ST) are proposed. Superposition of dipole and quadrupole is the mechanism behind shear-vortex coupling. Quadrupole mediated by tension perturbation reassesses shear-induced dilatation. Dipolar and quadrupolar characteristics is intrinsically correlated to local plasticity of MGs.